School and meal characteristics associated with plate waste in K-12 cafeterias in the United States. - Eunice S Adjapong; Kathryn E Bender; Sophia Schaefer; Brian E Roe (PLoS ONE)
Food wasted in primary and secondary education institutions creates nutritional losses, financial inefficiencies, and environmental degradation. While there is some evidence of how particular interventions within schools may influence the amount of waste created, there is little recent information about typical levels of food waste generated in U.S. primary and secondary schools and how waste correlates with school and meal characteristics. We analyze data reported by more than 100 schools from 24 states as part of the World Wildlife Fund's Food Waste Warriors project and identify how plate and beverage waste from school lunches are associated with school and meal service characteristics. We find schools that permit students to choose their own amount of milk report 76% less milk waste than those reliant upon individual milk cartons while schools that implement at least one non-curricular intervention (e.g., a table where students can share unopened food) report significantly less produce waste than other schools. We confirm several patterns observed or hypothesized in the literature, including more waste generated by younger students and during the earliest and shortest lunch periods. We document several novel associations including more plate waste at smaller schools, during winter months and in the Northeast region. We find several nuanced patterns of waste related to the prevalence of free and reduced meal service and whether all meal elements are offered versus served. While this study cannot support rigorous evaluation of intervention effectiveness, it provides insights into school and program characteristics that may pose challenges for schools interested in reducing student plate waste.